SEIQR-SIS epidemic network model and its stability - Wannika Jumpen (2018)
In this paper, we propose an SEIQR-SIS epidemic network model to study pandemic influenza and derive the approximate threshold condition (basis reproductive number) to examine the stability of the model. The numerical simulation of the disease transmission in the adaptive social network with people nodes and hub nodes is presented. The network parameters including visiting probability, hub radius and contact radius are used to investigate their impacts on the disease transmission. Our results show that these network parameters have a significant effect on the disease spread.